Strategi Komunikasi Tokoh Agama dalam Membina Kerukunan Antar Umat Beragama di Desa Balun Kecamatan Turi Kabupaten Lamongan - Mohammad Azwar Anas; Ainur Rofiq (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2021)
In general, the Unitary State of the Republic of Indonesia is rich in cultural, ethnic, racial and religious diversity. In Indonesia, there are 6 recognized religions, namely Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism. They all live side by side in Indonesia. In order to maintain religious harmony, there have been many ways that have been applied by the government, as well as religious leaders. However, the reality is that there are many cases of inter-religious cases in Indonesia. In Balun Village, Turi Subdistrict, Lamongan Regency, there are 3 religions, namely, Islam, Christianity, and Hinduism. The three religions live side by side while maintaining a close sense of tolerance between their religious communities. This research is a field research that is research with data obtained from field activities. The location of the research was carried out in Balun Village, Turi Subdistrict, Lamongan Regency. In this study, the researchers used qualitative research, the researchers collected and analyzed data from interviews, observations and documentation of religious leaders in Balun village, Turi sub-district, Lamongan regency. The results of the study indicate that: (1) The communication established by religious leaders to their people for inter-religious harmony is by meeting directly with their people to maintain harmony whenever and wherever they are. (2) the supporting factors of religious leaders in the village of balun are support from the village government and the condition of the people who are already accustomed to it. The inhibiting factor is that during a pandemic like this, interactions between diverse people rarely occur. So it is feared that there will be friction between religious communities.